Aligarh Government of Uttar Pradesh - Planning Commission (Planning Commission)
The need for planning in any field of human activity is self-evident and we in this country have taken the pledge to raise ourselves to higher levels of social and economic prosperity by directing our resources rationally. The programme for the whole country in this behalf is given in the first Five-Year Plan, drawn up by the Planning Commission of the Government of India. the programme for Uttar Pradesh is outlined in the Plan of the State Government.
Information Directorate, U. P. Lucknow.